Odpowiedzi

  • Użytkownik Zadane
2009-11-05T14:28:07+01:00
4x3-3x-x4+2x3+3x=-x4+6x3
x4-2x3-3x+8x3-6x+4,5+3x-1=x4+6x3-6x+3,5
(4x3-3x)(-9-6x+2)+x4-2x3-3x=-36x3-24x4+8x3+27x+18x2-3x+x4-2x3-3x=-23x4-30x3+18x2+21x
Najlepsza Odpowiedź!
2009-11-05T14:33:19+01:00
U(x)-W(x)=4x³-3x-(x⁴-2x³-3x)=4x³-3x-x⁴+2x³+3x=-x⁴+6x³

W(x)+2U(x)-1/2 V(x)=x⁴-2x³-3x+2(4x³-3x)-1/2(-3²-6x+2)=x⁴-2x³-3x+8x³-6x+3/2 x²+3x-1=x⁴+6x³+3/2 x²-6x-1

U(x) razy V(x)+W(x)=(4x³-3x)(-3x²-6x+2)+(x⁴-2x³-3x)=
-12x⁵-24x⁴+8x³+9x³+18x²-6x+x⁴-2x³-3x=-12 x⁵-23x⁴+15x³+18x²-9x
3 5 3
2009-11-05T16:52:15+01:00
U(x)-W(x)=4x³-3x-(x⁴-2x³-3x)=4x³-3x-x⁴+2x³+3x=-x⁴+6x³


W(x)+2U(x)-1/2 V(x)=x⁴-2x³-3x+2(4x³-3x)-1/2(-3²-6x+2)=x⁴-2x³-3x+8x³-6x+3/2 x²+3x-1=x⁴+6x³+3/2 x²-6x-1


U(x) * V(x)+W(x)=(4x³-3x)(-3x²-6x+2)+(x⁴-2x³-3x)=
-12x⁵-24x⁴+8x³+9x³+18x²-6x+x⁴-2x³-3x=-12 x⁵-23x⁴+15x³+18x²-9